2009
DOI: 10.3382/ps.2009-00087
|View full text |Cite
|
Sign up to set email alerts
|

Melamine residues in tissues of broilers fed diets containing graded levels of melamine

Abstract: An experiment was conducted to determine melamine residual levels in the tissues of broiler chickens fed diets containing graded levels of melamine. Ten experimental diets were developed to contain 0, 2, 5, 10, 20, 50, 100, 200, 500, and 1,000 mg of melamine/kg of diet. Each diet was offered in 4 replicate cages (12 birds per cage) from d 1 to 42, followed by a 7-d feeding of a withdrawal diet that contained no melamine. On d 28, 42, and 49, one bird per replicate was killed and tissue samples from the breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
16
2
Order By: Relevance
“…11 Lu et al reported the similar results in broilers. 12 But when MEL was administered daily at 10 g/animal, 2 sheep developed anorexia and died at approximately 16 and 31 days, respectively. 13 The difference between the finding in poultry and sheep may have been due to the level of MEL exposure.…”
Section: Discussionmentioning
confidence: 99%
“…11 Lu et al reported the similar results in broilers. 12 But when MEL was administered daily at 10 g/animal, 2 sheep developed anorexia and died at approximately 16 and 31 days, respectively. 13 The difference between the finding in poultry and sheep may have been due to the level of MEL exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we substituted similar scores to address whether there were sufficient dose groups (i.e., 1 control and at least 2 dose levels) and sufficient quantitative information (e.g., mean response, standard error or SD for mean responses, or survival counts) as necessary for BMD modeling. From the results of the data review, we identified 13 studies with data for 21 test endpoints for 4 avian species (Lu et al 2009;Gao et al 2010;Sirilaophaisan et al 2010Sirilaophaisan et al , 2011Brand 2011;Ding et al 2011;Yang et al 2011;Gallo et al 2012;Brand et al 2012;Landers et al 2012Landers et al , 2013Zhang et al 2012;Zapletal et al 2016). Within these studies, we examined multiple test endpoints for various exposure durations and test concentrations.…”
Section: Wildlife Bmd Analysis Case Studymentioning
confidence: 99%
“…These findings are in line with a previous study on tissue depletion in laying hens (Bai et al ., ). In contrast, earlier reports in broilers exposed to MEL showed higher MEL concentrations in the kidney than in the liver (Lu et al ., ). This difference with the present results may be due to the different treatment between the studies (multiple administrations over 28 and 42 days in chickens compared to a single dose in ducks), or to species specific differences.…”
Section: Resultsmentioning
confidence: 97%